The performance and egg quality traits of Nigerian local hens fed varying dietary levels of palm kernel cake with added palm oil (2012)
A total of 120 local hens at the point of lay were randomly assigned, 2 per cage, with 10 replicates per diet in a completely randomized design, to 6 palm kernel cake (PKC)-based layer diets that contained 20% CP and 2,700 kcal of ME/kg of feed. The PKC was included at levels of 10, 20, 30, 40, and 50% in diets 2, 3, 4, 5, and 6, respectively. Diet 1 without PKC served as the control. To make the diets isocaloric, 0.5, 1.48, 3.35, 5.22, 7.11, and 8.98% palm oil was added to diets 1, 2, 3, 4, 5, and 6, respectively. Feed and water were offered ad libitum for 12 wk. The hen-day production (53.8 to 63.3%) peaked at dietary PKC levels of 20 to 40%. Feed conversion ratio was also the lowest in hens fed the 20 to 40% PKC-based diets, but it was poorer than the control diet for those fed 50% PKC. The least hen-day production was obtained for birds on the 50% PKC-based diet. The albumen height (3.16 to 3.73 mm) was highest for eggs laid by hens fed the control and 10% PKC diets. The egg yolk indexes obtained for hens fed 0 to 10% dietary PKC (0.2) were significantly higher than those obtained for hens fed 20 to 50% PKC (0.13 to 0.15). The yolk color score increased significantly (P < 0.05) across the diets (from 1.0 to 5.9) as the level of palm oil increased. The egg weight, egg circumference, eggshell thickness, egg shape index, and weights of the albumen and yolk were similar across diets. Feeding up to 40% PKC with added palm oil had no adverse effect on the performance of Nigerian local hens and the quality of their eggs.